Transformación digital de la cadena de valor de la Empresa HRamirezP S.A. - Carrasco Ramírez, Cristina Gabriela (2023)
The digital transformation, which is planned to be carried out in the company HRamírezP S.A., is due to the fact that this factor has become a crucial issue for many organizations today, and it is due to various problems or challenges that they face in the business environment. . Therefore, the general objective was to design a model of digital transformation of the value chain of the piloting company H-RamírezP S.A. The methodology used was descriptive, with a mixed approach, where interviews and surveys were connected, the results of which confirm the need for the company to join the digitization of many processes in the value chain, it was also found that communication, It is the most necessary, according to the voices of employees and company administrators. The sample that was taken was from the same population of the company, a total of 128, who responded that it is essential that the company take into account the results of the cross-analysis to design strategies and concrete actions that address the concerns of the employees, promote the collaboration and improve efficiency and productivity in the value chain. The active participation of employees in the digital transformation process is essential to achieve success and maximize the benefits of digitalization in the port services company. The main conclusion was that with the plan detailed in the proposal, seek to guide the digital transformation process in our port services company in an effective and organized manner. The collaboration and commitment of all employees will be critical to the success of this initiative. As this transformation progresses, they will be better prepared to face the challenges of the future and remain leaders in the industry.